Effectiveness of Tai-Chi for Decreasing Acute Pain in Fibromyalgia Patients - Segura-Jiménez, V.; Romero-Zurita, A.; Carbonell-Baeza, A.; Aparicio, V. A.; Ruiz, J. R.; Delgado-Fernández, M. (International Journal of Sports Medicine, 2014)
Tai-Chi has shown benefits in physical and psychological outcomes in diverse populations. We aimed to determine the changes elicited by a Tai-Chi program (12 and 24 weeks) in acute pain (before vs. after session) in fibromyalgia patients. We also assessed the cumulative changes in pain brought about by a Tai-Chi program. Thirty-six patients (29 women) with fibromyalgia participated in a low-moderate intensity Tai-Chi program for 12 weeks (3 sessions/week). Twenty-eight patients (27 women) continued the program for an additional 12 weeks (i. e., 24 weeks). We assessed pain by means of a Visual Analogue Scale (VAS) before and after each single session (i. e., 72 sessions). We observed significant immediate changes (P-values from 0.037 to 0.0001) with an approximately 12% mean decrease of acute pain in the comparison of VAS-values before and after each session (72 sessions in total), with the exception of 4 sessions. We observed significant changes in cumulative pain pre-session (95% CI=−0.019; −0.014; P<0.001) and cumulative pain post-session (95% CI=−0.021; −0.015; P<0.001) along the 24-week intervention only. In conclusion, a low-moderate intensity Tai-Chi program for 12 weeks (3 times/week) decreased levels of acute pain in fibromyalgia patients. A longer period is necessary (e. g. 24 weeks) for observing cumulative changes in pain.
Keywords: immediate pain; cumulative pain; low-moderate intensity; visual analogue scale; alternative therapy; exercise